2001
DOI: 10.1086/321137
|View full text |Cite
|
Sign up to set email alerts
|

Ellipsoidal Collapse and Previrialization

Abstract: We study the non-linear evolution of a dust ellipsoid, embedded in a Friedmann flat background universe, in order to determine the evolution of the density of the ellipsoid as the perturbation to it related detaches from general expansion and begins to collapse. We show that while the growth rate of the density contrast of a mass element is enhanced by the shear in agreement with Hoffman (1986a), the angular momentum acquired by the ellipsoid has the right magnitude to counterbalance the effect of the shear. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 40 publications
5
37
0
Order By: Relevance
“…This result is in agreement with Peebles (1990). The quoted controversy was addressed by Del Popolo et al (2001) who examined the evolution of non-spherical inhomogeneities in a Einstein-de Sitter universe, by numerically solving the equations of motion for the principal axes and the density of a dust ellipsoid. They showed that for lower values of ν (ν = 2) the growth rate enhancement of the density contrast induced by the shear is counterbalanced by the effect of angular momentum acquisition.…”
Section: Introductionsupporting
confidence: 71%
“…This result is in agreement with Peebles (1990). The quoted controversy was addressed by Del Popolo et al (2001) who examined the evolution of non-spherical inhomogeneities in a Einstein-de Sitter universe, by numerically solving the equations of motion for the principal axes and the density of a dust ellipsoid. They showed that for lower values of ν (ν = 2) the growth rate enhancement of the density contrast induced by the shear is counterbalanced by the effect of angular momentum acquisition.…”
Section: Introductionsupporting
confidence: 71%
“…However, the description of matter as a pressureless ideal fluid will break down on small scales when non-linear structures form, due to shell-crossing. After any vorticity is generated in gravitational collapse [107], it will be amplified by the collapse, and will formally diverge at the same time as the density [108]. A static dust structure, with θ = 0, is possible only if large amounts of vorticity are present, as (2) shows: vorticity has to balance the contribution of both the energy density and the shear on the right-hand side.…”
Section: The Local Equationsmentioning
confidence: 99%
“…However, before we can make use of such a formula, we must relate the statistical quantities and h() to and h SC (). It is well known that (Padmanabhan 1996(Padmanabhan , 2002Peebles 1980;Padmanabhan & Engineer 1998;Del Popolo et al 2001;Padmanabhan & Ray 2006), on scales smaller than the size of the collapsing objects and around high density peaks,…”
Section: Modeling Nonlinear Structuresmentioning
confidence: 99%